Examining Teachers’ Technological, Pedagogical, and Content Knowledge (TPACK) in Remote Teaching and Learning Modality - Honra, Joelash R. (Future Science / FSH-PH Publications, 2022)
This study examined the teachers’ technological, pedagogical, and content knowledge (TPACK) in the remote teaching and learning modality. Specifically, it sought to find out if gender (male and female) and age groups (Gen Z, Millenial, and Gen X) have significant differences in the respondents’ TPACK skills and if their attendance in the in-service training could cause a significant change in the perceptions of the said skills. The study followed the quantitative survey research design. An adapted research instrument was used to evaluate respondents’ perceptions of TPACK abilities during the remote teaching and learning modality. The Mann-Withney u test was used to determine if the gender (male and female) would significantly differ in TPACK. While Kruskal-Wallis H test was used to analyze if the age groups (Gen Z, Millennial, and Gen X) show significant differences in the respondents’ TPACK skills. To assess a significant change in the respondents’ attendance in the in-service training, the McNemar change test was used. The study sample comprised 60 teachers from several public high schools in Makati City teaching remotely during the pandemic. Based on the results, gender did not show a significant difference in the TPACK abilities of the respondent. While no significant difference was established among the age groups regarding their TPACK skills, one domain (technological knowledge) of TPACK revealed significant results among the age groups. Moreover, it was also proven that respondents showed significant changes in their TPACK skills before and after attending the in-service training. Therefore, this study recommends creating learning communities among teachers of different gender and age groups to share their best practices during the remote learning setup to help improve others' TPACK skills. Also, it is recommended that the school administrations prioritize teachers’ professional development by providing them with vital training and seminars to improve the said skills.